دراسة تحليلية لاستخدام المنصات التعليمية الإلكترونية على عينة من المتعلمين في مرحلة التعليم المتوسط 2022-2023 (El-Wahat Journal for Research and Studies, 2025)
his study aims to identify the reality of the use of       e-leaning platforms in Algeria for the middle school stage, through a sample of learners. To achieve the objectives  of the study, the researcher conducted scientific interviews that serve the questions and objectives of the study, which were answered by a sample of 60 learners.The researcher used the descriptive analytical approach to answer the study's questions, where she concluded that there is a lack of use of e-leaning platforms by learners, due to the fact that the available platforms do not meet their educational needs. Key words: Usage, E-leaning platforms, Middle School learners.